Presbiterianismo em Jundiaí: história e organização tardia - Martins, Thales Renan Augusto (2015)
This research aims to investigate the diffusion of Presbyterianism in Jundiai (SP) and the causes of the late organization of the Presbyterian Church of Jundiai in 1951. The first chapter looks at the emergence of Presbyterianism in Europe in the sixteenth century and the path of the name until his arrival in Brazil in 1859. It also deals with the development of Presbyterianism in St. Paul and the missionary preaching in the region. The second chapter deals with the city of Jundiai: history, population characteristics, development, among others. Notes the Catholic presence in much of the population and how this fact has become an obstacle to Presbyterianism in the locality. The third and final chapter discusses in more detail the diffusion of Presbyterianism in Jundiaí to the organization of the First Presbyterian Church in the city in the year 1951. The reasons for the late organization also are in the chapter.